JATI DIRI: YANG NASIONALIS DAN YANG RELIGIUS DALAM BINGKAI KEWARGANEGARAAN - Bernard Subang Hayong (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2013)
Identity, as what defines one’s self directly, touches on the question of human existence: how we identify ourselves and affirm our identity and group admist plural reality as with the nation of Indonesia. Indonesian citizens affirm their identity which is religious and at the same time national. As citizens, on the one hand, we give rational reasons when making political demands, and not simply emotional preferences. On the other hand these reasons have a public quality, that is need to be capable of convincing people of various beliefs and nations. For this to take place there needs to be a discernment process between what is a personal faith matter and those convictions that need to be defended in the public square. Kata-kata Kunci: Jati diri, negara, agama, nalar publik, kesadaran, dialog, pluralitas.